2014
DOI: 10.1093/pubmed/fdu062
|View full text |Cite
|
Sign up to set email alerts
|

Racial/ethnic and gender differences in the association between depressive symptoms and higher body mass index

Abstract: Women had a higher BMI than men, and depressive symptoms were more strongly associated with BMI among African Americans and women than among non-Latino Whites and men. Tailored interventions to alleviate depressive symptoms in African Americans and females may help decrease racial/ethnic and gender differences in depressive symptoms and obesity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
22
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(29 citation statements)
references
References 33 publications
6
22
1
Order By: Relevance
“…These findings coincide with the results of other studies on the differential effects of the association between obesity and major depressive disorder by race and gender (Gavin et al, 2010; Hicken et al, 2013; Assari, 2014a,b,c; Assari and Caldwell, 2015; Hawkins et al, 2015; Kodjebacheva et al, 2015). The results of this study in Black men and women are in agreement with a number of studies examining the “Jolly Fat” hypothesis, which supports that higher body mass index and obesity in women is associated with less depression (Jasienska et al, 2005; Kim et al, 2010; Yu et al, 2011).…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…These findings coincide with the results of other studies on the differential effects of the association between obesity and major depressive disorder by race and gender (Gavin et al, 2010; Hicken et al, 2013; Assari, 2014a,b,c; Assari and Caldwell, 2015; Hawkins et al, 2015; Kodjebacheva et al, 2015). The results of this study in Black men and women are in agreement with a number of studies examining the “Jolly Fat” hypothesis, which supports that higher body mass index and obesity in women is associated with less depression (Jasienska et al, 2005; Kim et al, 2010; Yu et al, 2011).…”
Section: Discussionsupporting
confidence: 91%
“…Previous cross-sectional (Gavin et al, 2010; Hicken et al, 2013; Assari, 2014a,c; Assari and Caldwell, 2015; Kodjebacheva et al, 2015) and longitudinal (Hawkins et al, 2015) research had shown that the link between obesity and depressive symptoms depends on the intersection of race and gender (Assari, 2014b). The way in which physical activity shapes our perceived health is, however, universal.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…49,50 Anxiety and depression are more common in women than men, 51,52 and in adults, obesity is more strongly associated with anxiety and depression in women compared with men. 51,53 There are few human data regarding sex differences in the impact of maternal obesity on risk of anxiety and depression in offspring. 54,55 Because of the potential for confounding, a direct effect of maternal obesity on offspring anxiety-like and depressive behaviors may be more easily evaluated using animal models (see later).…”
Section: Anxiety and Depressionmentioning
confidence: 99%
“…The highest BMI level in men relative to women was observed in a large Western European sample [ 4 ] as well as in a Central European sample [ 5 ]. In contrast, Kodjebacheva, Kruger, Rybarczyk and Cupal [ 6 ] found that African American women had a higher BMI than African American men. Meanwhile, Furthner et al [ 7 ] demonstrated a lack of gender differences in BMI in the youngest age group (aged 10–14) of their study, yet BMI during adolescence (at the age of 17) was higher in boys and significantly decreased in girls.…”
Section: Introductionmentioning
confidence: 97%